Divided government versus incumbency externality effect: Quasi-experimental evidence on multiple voting decisions - Florian Ade; Ronny Freier (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper explores the interdependency of political institutions from the voter's perspective. Specifically, we are interested in: (1) Does the partisan identity of the mayor influence the voter's decision in the subsequent town council election?; (2) Does this partisan identity influence the vote in ensuing higher level elections?; and (3) Do voters condition their vote for the mayor on the result of the last council election? We rely on a regression discontinuity design focusing on close election outcomes based on municipal level data for Germany. We find (1) that the party of the mayor can receive a bonus of 4-6 percentage points in vote share in the next town council election (depending on the timing of the local elections). (2) The mayor partisan identity does not affect federal or European election outcomes within the same municipality. And (3), we show that voters punish mayor candidates of parties that performed strongly in earlier council elections. Throughout the paper, we explore how the findings can be related to an incumbency externality effect and to the theory of voter preferences for divided government.
Keywords: H10; H11; H77; 330; regression discontinuity design; municipality data; local election results; divided government effect; incumbency externality effect; Wahlverhalten; Kommunalwahl; Politische Partei; Externer Effekt; Wahl; Deutschland